Buku Ilustrasi Interaktif Tari Thengul Khas Bojonegoro Sebagai Media Pengenalan Pada Anak - Masnuna; Danna Norisa Putriyani; Aditya Rahmanyani (Jurnal Ilmu Komputer dan Desain Komunikasi Visual, 2020)
Thengul dance is a traditional art that must be preserved so that it does not become extinct and result in the loss of the identity of an area. Thengul dance is gaining attention from the national scene due to various achievements, this is an interesting phenomenon. Children must be introduced to the arts of their area early on, so that the rising phenomenon does not end just like that. Introducing traditional arts to children must use interesting media. An interesting and interactive media is needed so that children do not get bored while studying Culture, because many people think that traditional art is less interesting. Interactive illustrated books will be an effective media to introduce Thengul dance to children in Bojonegoro district. There are two stages of the method carried out, the first stage of preparation which includes data collection, data analysis, synthesis and determination of design objects. Then the second stage of creation which includes the stages of pre-production, production and post-production. Using this method will produce a design concept with the keyword "witty Thengul dance expression", which is getting to know Thengul dance in an exciting and interesting way. With these keywords can be used as a reference in the design of the book let's learn Thengul dance. Interactive illustrated book was made as a medium for introducing the tengul dance to children aged 6-9 years, so that children in the Bojonegoro district could participate in the preservation of regional arts later.